ON EQUIVARIANT MOVABILITY OF PLANE INVARIANT COMPACTS - Gevorgian, P. S. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2001)
The notion of movability was itroduced, for metrizable compacts, by K. Borsuk. He proved that the any plane compact is a movable. In this paper the equivariant movability of plane invariant compacts is studied. It is proved that all plane invariant compacts are equivariant movable in the case of linear action of compact and connected group G on the plane.